MORFOLOGI LARVA DAN POLA INFEKSI FALCAUSTRA KUTCHERI BURSEY ET.AL., 2000 (NEMATODA : COSMOCERCOIDEA: KATHALANIIDAE) PADA LEUCOCEPHALON YUWONOI (MCCORD ET.AL., 1995) DI SULAWESI TENGAH, INDONESIA - Purwaningsih, Endang; Riyanto, Awal (JURNAL BIOLOGI INDONESIA, 2011)
ABSTRACTMorphological Study of Larvae and Infection Pattern of Falcaustra kutcheri Bursey et.al.,2000 in Leucocephalon yuwonoi Mc Cord et.al., 1995 from Sulawesi. Some nematode parasitesFalcaustra kutcheri Bursey et.al., 2000 were found in alimentary tract of Leucocephalonyuwonoi, those were large in numbers in rectum and a small numbers in stomach. Both adultand larvae were collected from the host. The larvae were different on mouth structure and theshape of esophagus. An additional character, i.e two lateral branches of the anterior part ofintestine, that appear along the growth of larvae were reported.Key words: Nematode, Falcaustra kutcheri, infection pattern, larvae, morphology,Leucocephalon yuwonoi, Sulawesi